Ethnobotanical, phytochemical and biological activities of Nauclea latifolia Smith, an African medicinal plant harvested in Mali - (:unkn) unknown (My University, 2011)
Nauclea latifolia Smith (Rubiaceae) is a plant with curative virtues much more known in Sub-Saharan Africa in the traditional pharmacopoeia for the numerous biological activities. N. latifolia Sm.is a shrub or tree Soudano-Sahelian species ; his zones of abundance are in most cases Western and Central Africa. His wide use in traditional medecine incited us to realize an ethnobotany investigation and a phytochemical screening to put in coherence the prescriptions and the potential activities of the chemical constituents. The main classes of metabolites secondary sectors, maily alkaloids, flavonoids, tannins, sterols and terpenoids, were looked for in the leaves, barks of stems and roots. N. latifolia Sm. all over the presence of its numerous chemical families have interesting pharmacological activities. The extracts of existent complete alkaloids of the 3 organs of the plant, proved an anticancerous activities. These extracts inhibit the proliferation of the mammary cancerous cells MCF-7. Besides, activity antitumorale extracts alkaloids of N. latifolia Sm. act against pain. They inhibit the effect of pain after injection acetic acid in 0,6 % to the mice. However, N. latifolia Sm. comes as a plant in numerous drugs. With regard to the interesting biological activities, it is necessary to lead intense investigation to enrich the production of Traditional Ameliorated Drugs.
Keywords: African Research